Chronic traumatic encephalopathy: How serious a sports problem is it? - Tator, C. H. (British Journal of Sports Medicine, 2014)
It is now recognised that there is a spectrum of concussion disorders ranging from acute concussion at one end to various forms of brain degeneration at the other end. The spectrum includes acute concussion, second impact syndrome or acute cerebral swelling, postconcussion syndrome, depression or anxiety, chronic traumatic encephalopathy (CTE) and possibly other forms of central nervous system degeneration. It is essential to carefully evaluate the clinical and neuropathological correlations of CTE that have been published. This has been accomplished in an excellent paper on this subject by Gardner and colleagues in this issue. There have been significant advances in our knowledge of the clinical and neuropathological features of CTE in athletes in the past 10 years. However, we are just at the beginning of our appreciation of this entity due to the paucity of research and the inability to diagnose CTE during life. At present, it is not possible to assess the validity of the proposed methods of classification and grading of the severity of the disease. Additional studies of large numbers of at-risk athletes are essential, especially prospective longitudinal studies. Obviously, such studies would be even more effective if reliable in vivo biomarkers were discovered, especially non-invasive ones such as advanced MRI or MR spectroscopy or invasive ones such as blood or cerebrospinal fluid tests. The major questions that remain unanswered include the frequency of CTE in various collision sports, the causal or otherwise relationship between concussions and CTE, the number of concussions that need to be involved and their management.